Multifactorial positive influence of cochlear implantation on patients with single‐sided deafness. (22nd April 2019) - Häußler, Sophia M.; Köpke, Vanessa; Knopke, Steffen; Gräbel, Stefan; Olze, Heidi
Abstract : Objectives: Single‐sided deafness (SSD) is an extreme case with profound unilateral hearing loss in the poorer ear and regular hearing in the other ear. The aim of this study is to investigate the impairment in the daily life of SSD patients and the influence of cochlear implants (CI) on their health‐related quality of life (HRQoL), the impact on existing tinnitus distress and psychological comorbidities, and audiometric parameters. Methods: In total, 21 patients (8 male and 13 female) were included, and the Charité Test Battery was applied for all patients. Data on HRQoL were collected with the Nijmegen Cochlear Implant Questionnaire and the Medical Outcome Study Short Form 36 (SF‐36) Survey. Tinnitus distress was assessed with the Tinnitus Questionnaire (TQ). Data with regard to psychological comorbidities were collected using four validated questionnaires. Speech perception was assessed with the Freiburg Monosyllable Test (FMS), the Oldenburg Sentence Test (OLSA), and the Oldenburg Inventory (OI). Results: HRQoL improved in the subdomain social interactions. Tinnitus distress dropped significantly 6 months postoperatively. SSD patients preoperatively showed elevated levels of stress, depressive symptoms, and anxiety. Postoperatively, these psychological symptoms improved with regard to stress, tension, and demands. The audiometry tools revealed a significant improvement in directional hearing (OI), speech perception in silence, and in the speech intelligibility threshold (OLSA). Conclusion: There was an improvement in HRQoL and a reduction of tinnitus and cognitive distress. The preoperatively elevated stress level decreased significantly, and psychological comorbidities such as depressive symptoms and anxiety all improved postimplantation. Level of Evidence: II‐2 Laryngoscope, 130:500–506, 2020